PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN KERJASAMA SISWA KELAS III DI SDN 096 SARIJADI SELATAN, BANDUNG - Depin Depila; Effy Mulyasari; Eva Riyanti (STKIP Subang, 2023)
ABSTRACT One of the skills of the 21st century that must be possessed is the ability to collaborate or work together. Cooperation means working together to achieve the same goal. In the context of learning, cooperation is referred to as an activity aimed at group work between friends who have different opinions, but these differences of opinion can be put together This study aims to determine the application of the jigsaw-type of cooperative learning and also to increase student collaboration by using the jigsaw-type of cooperative learning model. This research is collaborative classroom action research with a qualitative descriptive approach consisting of two cycles. In this study, 31 students in class 3A at SDN 096 Sarijadi Selatan for the academic year 2022–2023 were used as research subjects. The data was collected through observations made during the learning process. The results of this study showed that there was an increase in student student cooperation in cycle 1, which obtained a result of 81.2% in the